2009
DOI: 10.1176/foc.7.3.foc374
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression and Antidepressant Treatment: Impact on Pregnancy and Neonatal Outcomes

Abstract: Objective-Selective serotonin reuptake inhibitor (SSRI) use during pregnancy incurs a low absolute risk for major malformations; however, other adverse outcomes have been reported. Major depression also affects reproductive outcomes. This study examined whether 1) minor physical anomalies, 2) maternal weight gain and infant birth weight, 3) preterm birth, and 4) neonatal adaptation are affected by SSRI or depression exposure.Method-This prospective observational investigation included maternal assessments at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 38 publications
2
104
4
2
Order By: Relevance
“…Research has established that pregnant women prefer nonpharmacological interventions and are reluctant to take medication because of fear of affecting their developing baby (Wisner et al, 2009) hence the importance of the availability of alternative, non-invasive, interventions for the prevention of PND. In contrast, little is known in general about the views and experiences of women taking part in preventive interventions and what the health care professionals delivering the interventions believe.…”
Section: Introductionmentioning
confidence: 99%
“…Research has established that pregnant women prefer nonpharmacological interventions and are reluctant to take medication because of fear of affecting their developing baby (Wisner et al, 2009) hence the importance of the availability of alternative, non-invasive, interventions for the prevention of PND. In contrast, little is known in general about the views and experiences of women taking part in preventive interventions and what the health care professionals delivering the interventions believe.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal stress due to psychopathological factors such as depression and anxiety during pregnancy may constitute a risk for adverse pregnancy and perinatal outcomes (Alder et al, 2007;Li et al, 2009;Lou et al, 1994;O´Connor et al, 2002;Rodriguez and Bohlin, 2005). A recent study by Wisner concluded that continuous untreated depression in pregnant women was associated with preterm birth rates exceeding 20 % (Wisner et al, 2009). Emerging research has also demonstrated that maternal stress during pregnancy can result in changes in the hypothalamic-pituitary-adrenal (HPA) axis and elevated levels of stress hormones (particularly cortisol) with premature labor, shortened pregnancy length, low birth weight and impaired fetal brain development as a consequence (Copper et al, 1996;Diego et al, 2006;Field et al, 2006;Gitau et al, 1998;Obel et al, 2005;Sandman et al, 1994;Wadhwa et al, 1993;Weinstock, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In one study 6 that compared SSRI-treated women with untreated depressed controls, there was no increase in risk. In the only study to date that described propensity-matching as a method to control for the presence and severity of maternal depression, Oberlander et al 18 found that both the duration of gestation and the risk of preterm delivery did not differ significantly between depressed women who had used SSRIs during pregnancy and those who had not.…”
Section: Ssris and Preterm Deliverymentioning
confidence: 97%
“…Some, [1][2][3][4][5][6][7][8][9][10] but not all, [11][12][13][14][15][16][17] studies suggest that the use of SSRIs during pregnancy increases the risk of preterm delivery; in the positive studies, the risk appears to be approximately doubled, on average, in SSRIexposed relative to unexposed women. An important limitation of these studies is that all were observational in design.…”
Section: Ssris and Preterm Deliverymentioning
confidence: 99%